Teacher's Efforts on the Ability to Read Aloud for Class V Students with the Cooperative Script Method in Indonesian Language Subjects in Elementary Schools: Upaya Guru pada Kemampuan Membaca Nyaring Siswa Kelas V dengan Metode Cooperative Script pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Kharisma, Juhi Putri; Liansari, Vevy (Universitas Muhammadiyah Sidoarjo, 2023)
Reading aloud is an activity that makes a tool for teachers, students or readers and listeners to capture and understand information from the readings delivered by students. The researcher applies the cooperative script method for students. Cooperative learning is a type of group work including forms of activities that are guided and directed by the teacher. Cooperative learning prioritizes cooperation in solving problems to apply knowledge and skills in order to achieve learning objectives. As well as a learning method in which students work in pairs and take turns orally summarizing the parts of the material being studied. The purpose of this study was to find out the efforts made by the teacher for how to read aloud students while at school. This research is a descriptive qualitative type.